2018
DOI: 10.1016/j.reval.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Peamacléine Pru p 7 : épidémiologie, implications cliniques et place dans le diagnostic moléculaire de l’allergie à la pêche en région méditerranéenne

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…We have previously described a ubiquitous co‐sensitization to CP in Pru p 7 sensitized individuals . Among the 171 Pru p 7 sensitized subjects in the present study, all but one, who had Pru p 7 IgE at the positivity threshold of the assay (0.10 kU A /L), were also sensitized to CP.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…We have previously described a ubiquitous co‐sensitization to CP in Pru p 7 sensitized individuals . Among the 171 Pru p 7 sensitized subjects in the present study, all but one, who had Pru p 7 IgE at the positivity threshold of the assay (0.10 kU A /L), were also sensitized to CP.…”
Section: Resultssupporting
confidence: 51%
“…Indeed, we found that Pru p 7 sensitization was associated with reactions to an array of plant foods, including but not limited to Rosaceae . Members of the GRP family are widely distributed in the plant kingdom, share high levels of sequence identity and have been associated with particularly severe food allergic reactions in at least three environments: Italy, France and Japan …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cup s 7 et Pru p 7 sont à l'origine de réactions croisées permettant d'expliquer les syndromes cyprès-pêche et cyprès-agrumes [35,36]. La sensibilisation au seul allergène Pru p 7 de la pêche est retrouvée chez plus de la moitié des patients allergiques à la pêche et est associée à une exposition au pollen de cyprès méditerranéen (Cupressus sempervirens) [37]. De plus les expériences d'inhibition réciproque et de stimulation ex vivo des polynucléaires basophiles de patients allergiques sont en faveur d'un rôle déterminant de la pollinose au cyprès dans l'allergie sévère à la pêche [38].…”
unclassified